Exploratory analyses of factors related to 5-aminolevulinic acid-induced intraoperative hypotension during malignant glioma surgery via literature review - Kyoichi Tomoto; Akihiko Teshigawara; Tomohiro Aoki; Masahiko Itani; Yuzuru Hasegawa; Yuichi Murayama; Toshihide Tanaka (Photodiagnosis and Photodynamic Therapy)
Background: Photodynamic diagnosis using 5-aminolevulinic acid (5ALA) improves glioma resection but has been associated with intraoperative hypotension (IOH), particularly in Japan. Although nitric oxide (NO) production has been suggested as a mechanism, the pathophysiology remains unclear. Methods: We retrospectively analyzed 148 glioma patients who underwent surgery between 2015 and 2024, comparing 5ALA(+) and 5ALA(-) groups in terms of IOH incidence and potential contributing factors, including age, body mass index, antihypertensive drug use, anesthesia duration, and extent of resection. IOH was defined as a mean arterial pressure <60 mmHg after induction. We also assessed phosphorylation of endothelial NO synthase (eNOS) in surgical specimens using immunofluorescence. Results: IOH occurred in 88.9 % of the 5ALA(+) group and 82.9 % of the 5ALA(-) group (p = 0.296). Elderly patients (>60 years old) and those using angiotensin II receptor blockers (ARBs) showed significantly higher IOH incidence in the 5ALA(+) group. Immunofluorescence revealed no detectable phospho-eNOS expression in tumor tissues, regardless of IOH presence. Conclusions: Our findings confirm previously reported risk factors for 5ALA-induced IOH, including older age and ARB use. The lack of eNOS expression in glioma tissues suggests that systemic, rather than tumoral, endothelial responses may mediate IOH via heme-dependent NO synthesis. Further studies using non-tumor tissues or experimental models are needed to elucidate the precise mechanisms and potential interactions between ARBs and 5ALA metabolism.